2010
DOI: 10.1152/physrev.00018.2008
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoplasmic Reticulum Function in Smooth Muscle

Abstract: The sarcoplasmic reticulum (SR) of smooth muscles presents many intriguing facets and questions concerning its roles, especially as these change with development, disease, and modulation of physiological activity. The SR's function was originally perceived to be synthetic and then that of a Ca store for the contractile proteins, acting as a Ca amplification mechanism as it does in striated muscles. Gradually, as investigators have struggled to find a convincing role for Ca-induced Ca release in many smooth mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
134
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 153 publications
(142 citation statements)
references
References 798 publications
2
134
0
1
Order By: Relevance
“…Indeed, the results of early experiments conducted on permeabilized strips of portal vein, pulmonary artery and taenia caeci suggested the existence of two separate calcium stores: Sa expressing both RyRs and IP3Rs and Sb expressing only IP3Rs. The contribution of the Sb store to IP3-induced Ca 2+ release was estimated to be 60% in taenia caecum, 40% in pulmonary artery and only 6% in portal vein (reviewed in Wray and Burdyga, 2010). In contrast, the results of more recent experiments conducted on isolated pulmonary artery myocytes suggested that IP3-releasable and caffeine-releasable calcium stores are virtually completely separate (Janiak et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Indeed, the results of early experiments conducted on permeabilized strips of portal vein, pulmonary artery and taenia caeci suggested the existence of two separate calcium stores: Sa expressing both RyRs and IP3Rs and Sb expressing only IP3Rs. The contribution of the Sb store to IP3-induced Ca 2+ release was estimated to be 60% in taenia caecum, 40% in pulmonary artery and only 6% in portal vein (reviewed in Wray and Burdyga, 2010). In contrast, the results of more recent experiments conducted on isolated pulmonary artery myocytes suggested that IP3-releasable and caffeine-releasable calcium stores are virtually completely separate (Janiak et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Either of these events, which cause an initial rise in [Ca 2+ ]i, may be further augmented by ryanodine receptor (RyR)-mediated Ca 2+ release activated via a Ca 2+ -induced Ca 2+ release (CICR) mechanism (Fabiato and Fabiato, 1975). However, the recruitment of RyR-mediated Ca 2+ release by voltage-gated Ca 2+ entry and/or IP3R-mediated Ca 2+ release in smooth muscles is still an area of extensive debate and controversy (reviewed in Laporte et al, 2004;Wray and Burdyga, 2010). Indeed, the relative contribution of RyRs and IP3Rs to intracellular [Ca 2+ ]i mobilization varies in different types of SMCs, and often depends on the strengths and mechanism of SMC stimulation.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations